Knowledge management system architecture for organizational learning with collaborative environment - Abdullah, Rusli; Sahibuddin, Shamsul; Alias, Rose Alinda; Mohd. Hasan, Selamat (2005)
Knowledge management system (KMS) is one of the most critical weapon to transform knowledge resources in organization into intellectual capital for competitive advantage. However, learning organizations (LO) still have difficulties in identifying an appropriate KMS architecture framework and KMS technologies for their organizations. There is also no clear mechanism on how to motivate and encourage a community of practice (CoP) to share and reuse knowledge, as well as to generate new knowledge in a collaborative environment. Therefore, this research aims to overcome these problems by developing a KMS model and architecture that would ensure the right knowledge could be acquired from and disseminated to the right people at the right time. A survey to a group of CoP was conducted to identify requirements as a basis for setting up a KMS model. The KMS model was used to develop a KMS architecture. The KMS architecture consists of an application layer, a technology layer, an infrastructure layer and a repository layer. This architecture was tested by developing a KMS prototype for a research and development CoP in a Public Higher Learning Institution (PHLI) LO. The system was developed by integrating Lotus Notes Script and JavaScript, which ran over an Intranet and Internet infrastructure. Agent technology was used in the system for profiling, notification, alert and monitoring. Another questionnaire survey was conducted after the KMS prototype implementation to verify the functionality of the system in facilitating knowledge sharing in a collaborative environment. The findings from both questionnaire surveys were compared to identify the effectiveness of KMS implementation in creating a collaborative environment for knowledge sharing, re-use and creation in a CoP. The study found that the use of agent technology in a KMS supports the creation of a collaborative environment in a CoP.